Grunt : the curious science of humans at war - Roach, Mary (W.W. Norton & Company, Inc., 2016)
"'Grunt' tackles the science behind some of a soldier's most challenging adversaries-- panic, exhaustion, heat, noise-- and introduces us to the scientists who seek to conquer them"--